2022
DOI: 10.1093/eurjpc/zwac185
|View full text |Cite
|
Sign up to set email alerts
|

Incidental coronary calcium in cancer patients treated with anthracycline and/or trastuzumab

Abstract: Background Cancer patients are at increased risk of cardiovascular disease (CVD) after treatment with potentially cardiotoxic treatments. Many cancer patients undergo non-gated chest CT (NCCT) for cancer staging prior to treatment. Aims We aimed to assess whether coronary artery calcification (CAC) on NCCT predicts CVD risk in cancer patients. Methods 603 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In addition to above-mentioned biomarkers, other potentially promising biomarkers are currently under investigation for their utility in the detection and/or prediction of CTRCD including: coronary artery calcification [ 298 ], endothelin-1 [ 299 ], neuregulin-1 [ 285 , 300 ], plasma bioactive adrenomedullin (ADM) [ 301 ], fragmented QRS (fQRS) [ 302 ], D-dimer [ 303 ], soluble fms-like tyrosine kinase receptor (sFlt)-1 [ 105 ], soluble ST2 (sST2) [ 145 , 149 , 171 , 279 , 304 ], CK-MB [ 134 , 286 ], topoisomerase II α gene ( TOP2A ) [ 305 ], cardiac myosin light chain 1 (cMLC-1) [ 306 ], vascular endothelial growth factor (VEGF) [ 93 ], placental growth factor (PIGF) [ 93 , 98 ], procollagen-derived type-I C-terminal-propeptide (PICP) [ 307 ], epicardial adipose tissue (EAT) volume [ 308 , 309 ], circulating bilirubin [ 310 ], hemopexin [ 311 ], glycated hemoglobin (HbA(1)c) [ 103 ], advanced oxidation protein products (AOPP) [ 102 ], human resistin [ 312 ] and vascular adhesion molecule 1 (VCAM-1) [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to above-mentioned biomarkers, other potentially promising biomarkers are currently under investigation for their utility in the detection and/or prediction of CTRCD including: coronary artery calcification [ 298 ], endothelin-1 [ 299 ], neuregulin-1 [ 285 , 300 ], plasma bioactive adrenomedullin (ADM) [ 301 ], fragmented QRS (fQRS) [ 302 ], D-dimer [ 303 ], soluble fms-like tyrosine kinase receptor (sFlt)-1 [ 105 ], soluble ST2 (sST2) [ 145 , 149 , 171 , 279 , 304 ], CK-MB [ 134 , 286 ], topoisomerase II α gene ( TOP2A ) [ 305 ], cardiac myosin light chain 1 (cMLC-1) [ 306 ], vascular endothelial growth factor (VEGF) [ 93 ], placental growth factor (PIGF) [ 93 , 98 ], procollagen-derived type-I C-terminal-propeptide (PICP) [ 307 ], epicardial adipose tissue (EAT) volume [ 308 , 309 ], circulating bilirubin [ 310 ], hemopexin [ 311 ], glycated hemoglobin (HbA(1)c) [ 103 ], advanced oxidation protein products (AOPP) [ 102 ], human resistin [ 312 ] and vascular adhesion molecule 1 (VCAM-1) [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several studies in this review included metastatic breast cancer patients amongst their target population and investigated the potential of emerging biomarkers in the detection of CTRCD in these patients [ 128 , 130 , 183 , 222 , 255 , 298 , 304 , 329 ]. Noticeably, some of these studies, have highlighted the differential expression of specific biomarkers (e.g., sFas, sFasL, NT-proBNP) in metastatic breast cancer patients compared to non-metastatic [ 104 , 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 24% of patients CAC score was above zero and one in three patients with high CAC score had no other CVD risk factors [ 27 ]. A retrospective study by Hooks et al has shown that CAC extent was a significant predictor of the coronary composite outcome, but not of the heart failure composite outcome [ 28 ]. On the other hand, in a multi-center cohort of 66,636 asymptomatic adults without cardiovascular disease (CVD), high CAC predicted the risk of death from CVD in official death certificates, independently of CVD risk factors [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with lung cancer undergo non-gated chest CT scans for cancer staging and surveillance. Incidental detection of coronary artery calcification is prevalent and can be helpful in providing CAD risk stratification and guiding prevention strategies ( 83 ). BP measurements that are routinely performed at oncology visits should be assessed and followed for the screening and monitoring of hypertension ( 84 ).…”
Section: Cardiovascular Disease Screening and Surveillance In Patient...mentioning
confidence: 99%